2022
DOI: 10.3390/su14063312
|View full text |Cite
|
Sign up to set email alerts
|

Plan and Develop Advanced Knowledge and Skills for Future Industrial Employees in the Field of Artificial Intelligence, Internet of Things and Edge Computing

Abstract: Knowledge and skills in the field of Artificial Intelligence (AI), Internet of Things (IoT), and Edge Computing (EC) are more and more important for industry. Therefore, it is crucial to know what current students and future employees can offer to the industry. University students develop their knowledge and skills to support the industry in implementing modern technologies in the future. It can be expected that the first source of information for students will be lectures and other activities at the universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…In [ 32 ], Paśko et al surveyed 563 students mainly from European countries about their knowledge and skills in the area of IoT, AI, and EC. The authors concluded that students are familiar with AI technologies while they have a lack of education in the field of EC.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In [ 32 ], Paśko et al surveyed 563 students mainly from European countries about their knowledge and skills in the area of IoT, AI, and EC. The authors concluded that students are familiar with AI technologies while they have a lack of education in the field of EC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, many studies on Industry 4.0 readiness from a higher education perspective come from non-EU countries [ 34 , 35 , 39 , 40 , 41 ]. Those assessing in Europe the level of preparedness of students for I4.0 may need a broader European view, as they focus on individual countries such as Germany [ 29 , 30 ] and Italy [ 31 ] or cover only a few European countries [ 32 ]. Moreover, such studies may need updating since, in the meantime, the requested skills and university programs may have been changed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In work [28], the authors assess topics included in the university curricula that may facilitate the implementation of Industry 4.0 solutions. Moreover, the work [29] presents how future employees (students) assess their own competencies in this area.…”
mentioning
confidence: 99%